The Role of Contact in the Origins of the Japanese and Korean Languages - Unger, J. Marshall (University of Hawaii Press, 2023)
Despite decades of research on the reconstruction of proto-Korean-Japanese (pKJ), some scholars still reject a genetic relationship. This study addresses their doubts in a new way, interpreting comparative linguistic data within a context of material and cultural evidence, much of which has come to light only in recent years. The weaknesses of the reconstruction, according to J. Marshall Unger, are due to the early date at which pKJ split apart and to lexical material that the pre-Korean and pre-Japanese branches later borrowed from different languages to their north and south, respectively. Unger shows that certain Old Japanese words must have been borrowed from Korean from the fourth century C.E., only a few centuries after the completion of the Yayoi migrations, which brought wet-field rice cultivation to Kyushu from southern Korea. That leaves too short an interval for the growth of two distinct languages by the time they resumed active contact.